Hypolestes hatuey sp. nov.: a new species of the enigmatic genus Hypolestes (Odonata, Hypolestidae) from Hispaniola - Torres-Cambas, Yusdiel; Lorenzo-Carballa, M. Olalla; Ferreira, Sónia; Cordero-Rivera, Adolfo (Zootaxa, 2015)
Both sexes of Hypolestes hatuey Torres-Cambas, sp. nov. (Odonata: Zygoptera: Hypolestidae) from Hispaniola are described and illustrated here. This newly described species differs from H. trinitatis and H. clara, the other two species within the genus, by the morphology of the genital ligula and male cerci. Females of H. hatuey sp. nov. differ from H. clara by the shape of the female antehumeral stripe and wing venation. Morphological distinctiveness in males is supported by genetic differences in the 16S mitochondrial gene. Following the categories and criteria of the IUCN Red List of Threatened Species, we suggest this species should be listed as Data Deficient (DD), given that available data on its distribution are too limited to assess its risk of extinction.